Framework Maths 9 A - Allan, Ray; Williams, Martin; perry,Claire (New York : Oxford University Press, 2005)
Talks about prior learning points; learning objectives; and explanations covered with examples, showing the key techniques. The units in this book also provide practice with questions pitched at the level suggested in the Framework; and summaries and review questions to help students gain responsibility for their learning.
Keywords: Juvenile works Mathematics; Mathematics Juvenile literature; Mathematics Problems exercises; Ouvrages pour la jeunesse; Problems and exercises